Addition of Active Dry Yeast Could Enhance Feed Intake and Rumen Bacterial Population While Reducing Protozoa and Methanogen Population in Beef Cattle - Kampanat Phesatcha; Krittika Chunwijitra; Burarat Phesatcha; Metha Wanapat; Anusorn Cherdthong (Fermentation, 2021)
Urea–lime-treated rice straw fed to Thai native beef cattle was supplemented with dry yeast (DY) (Saccharomyces cerevisiae) to assess total feed intake, nutrient digestibility, rumen microorganisms, and methane (CH4) production. Sixteen Thai native beef cattle at 115 ± 10 kg live weight were divided into four groups that received DY supplementation at 0, 1, 2, and 3 g/hd/d using a randomized completely block design. All animals were fed concentrate mixture at 0.5% of body weight, with urea–lime-treated rice straw fed ad libitum. Supplementation with DY enhanced total feed intake and digestibility of neutral detergent fiber and acid detergent fiber (p < 0.05), but dry matter, organic matter and crude protein were similar among treatments (p > 0.05). Total volatile fatty acid (VFA) and propionic acid (C3) increased (p < 0.05) with 3 g/hd/d DY supplementation, while acetic acid (C2) and butyric acid (C4) decreased. Protozoal population and CH4 production in the rumen decreased as DY increased (p < 0.05). Populations of F. succinogenes and R. flavefaciens increased (p < 0.05), whereas methanogen population decreased with DY addition at 3 g/hd/d, while R. albus was stable (p > 0.05) throughout the treatments. Thus, addition of DY to cattle feed increased feed intake, rumen fermentation, and cellulolytic bacterial populations.